Activity-dependent expression of Channelrhodopsin at neuronal synapses. Issue 1 (December 2017) - Gobbo, Francesco; Marchetti, Laura; Jacob, Ajesh; Pinto, Bruno; Binini, Noemi; Pecoraro Bisogni, Federico; Alia, Claudia; Luin, Stefano; Caleo, Matteo; Fellin, Tommaso; Cancedda, Laura; Cattaneo, Antonino
Abstract Increasing evidence points to the importance of dendritic spines in the formation and allocation of memories, and alterations of spine number and physiology are associated to memory and cognitive disorders. Modifications of the activity of subsets of synapses are believed to be crucial for memory establishment. However, the development of a method to directly test this hypothesis, by selectively controlling the activity of potentiated spines, is currently lagging. Here we introduce a hybrid RNA/protein approach to regulate the expression of a light-sensitive membrane channel at activated synapses, enabling selective tagging of potentiated spines following the encoding of a novel context in the hippocampus. This approach can be used to map potentiated synapses in the brain and will make it possible to re-activate the neuron only at previously activated synapses, extending current neuron-tagging technologies in the investigation of memory processes. Changes to subsets of dendritic spines are thought to be important for memory formation. Here, the authors develop a hybrid RNA/protein tool that allows for optogenetic stimulation of single synapses that have been tagged in an activity-dependent manner